Optical Imaging Modalities: Principles and Applications in Preclinical Research and Clinical Settings - Pirovano, Giacomo; Roberts, Sheryl; Kossatz, Susanne; Reiner, Thomas (The Journal of nuclear medicine (1978), 2020)
With the ability to noninvasively image and monitor molecular processes within tumors, molecular imaging represents a fundamental tool for cancer scientists. In the current review, we describe emergent optical technologies for molecular imaging. We aim to provide the reader with an overview of the fundamental principles on which each imaging strategy is based, to introduce established and future applications, and to provide a rationale for selecting optical technologies for molecular imaging depending on disease location, biology, and anatomy. To accelerate clinical translation of imaging techniques, we also describe examples of practical applications in patients. Elevating these techniques into standard-of-care tools will transform patient stratification, disease monitoring, and response evaluation.